The impact of the second victim phenomenon in an Italian Academic Hospital: a cross-sectional study. (20th October 2021) - Moretti, V; Scarpis, E; Ruscio, E; Bianchet, B; Doimo, A; Farneti, F; Castriotta, L; Quattrin, R; Cocconi, R
Abstract: Background: Adverse patient safety events (AEs) can negatively impact on healthcare workers (HCWs) by causing emotional distress and affecting professional ability. The challenge of healthcare organizations is to support HCWs involved in AEs. This study aims to investigate the second victim phenomenon in a large Italian Academic Hospital (AH). Methods: A cross sectional survey was conducted from June to November 2019 involving all HCWs working at the AH of Udine. HCWs' demographic characteristics and answers to the Second Victim Experience and Support Tool, Italian version (IT-SVEST; 29 items representing 7 dimensions and 2 outcome variables; Likert-scale: 1-5) were collected. Higher scores indicated a greater negative impact of the AEs and a perceived inadequacy of support resources. Median (M) and interquartile range (IQR) were assessed for each item. The agreement (AGR) (respondents with a mean score ≥4) was assessed for each dimension. Relationship between items score and demographic aspects was analyzed with non-parametric tests. Results: A total of 349 HCWs joined the survey. Women were 79.4% and mean age was 39.4±10.7 years. 58.7% of respondents referred to be involved in a AEs. Lots of HCWs expressed feelings of psychological distress (AGR=26.9%) and less experienced HCWs were more affected by feelings of shame than senior ones (M = 4, IQR=1.5 vs M = 3, IQR=2; p < 0.01). Physical distress (AGR=10.9%) and professional self-efficacy (AGR=11.8%) did not had a great impact on HCWs, but younger (M = 3, IQR=2 vs M = 2, IQR=2; p < 0.01) and female (M = 3, IQR=2 vs M = 2, IQR=2; p < 0.01) HCWs were more inclined to question their skills. Support services offered by Hospital organization may be improved (AGR 8, 9%). Conclusions: Psychological impact of the AEs is relevant in our cohort and less experienced and female HCWs resulted more inclined to doubt their professional abilities when involved. Improvements in support resources should be desirable to create a safer working environment. Key messages: HCWs' psychological dimension and perceived professional self-esteem can be negatively affected by adverse events, especially for less experienced and female professionals. Healthcare organizations need to develop and to implement a second victim support program designed to provide emotional, psychological and professional support for HCWs.